The Temperature Dependence of Ice Viscosity (Vyazkost Lda v Zavisimosti ot Temperatury) - Lavrov,V. V. (1950)
The role and significance of crystalline structure in the study of the plastic properties of ice has been demonstrated. An anomalous change in the rate of plastic deformation of specimens of sufficiently regular crystalline structure occurs when they are subjected to sharp change in temperature, constituting a phenomenon of interest to the theory of plasticity. It has been demonstrated that the phenomenon of rest, well known in the literature on crystallography, holds for ice as well. A sufficiently well-grounded evaluation of the relation between the viscosity of ice, and temperature is offered for the first time, within a temperature range of -3 degrees and -23 degress C. (Author) Trans. of Zhurnal Tekhnicheskoi Fiziki (USSR) v17 n9 p1027-1034 1947, by William Mandel.